The Powers of the Prosecutor General to Determine the Structure of the Prosecution Bodies: Constitutional and Jurisdictional Aspect - Stefanchuk , Maryna (Actual problems of law (Aktual'ni problemi pravoznavstva), 2025)
The article examines the problematic aspects of legislative regulation of the powers of the Prosecutor General to determine the structure of the prosecution bodies in Ukraine through the prism of the relevant case law of the Constitutional Court of Ukraine.It is stated that in the absence of a legal position of the court of constitutional jurisdiction on the constitutionality of the priority measures of reforming the prosecution bodies, problematic aspects of their staffing are addressed in the Decisions of the Constitutional Court of Ukraine on constitutional complaints of interested parties regarding the constitutional guarantees of the prosecutor’s independence.The author outlines one of such Decisions of the Constitutional Court of Ukraine recognised paragraph 9 of part one of Article 51 of the Law of Ukraine «On the Public Prosecutor's Office» as inconsistent with the Constitution of Ukraine, which regulates the following grounds for dismissal of a prosecutor: in case of liquidation or reorganisation of the prosecutor's office in which the prosecutor holds a position, or in case of reduction of the number of prosecutors in the prosecutor's office. According to the legal position of the Constitutional Court of Ukraine, under this clause of the Law of Ukraine «On Public the Prosecutor’s Office», the grounds for dismissal of a prosecutor from the position held in the prosecution body are not an individual act of law, but an organisational decision of the Prosecutor General on liquidation or reorganisation of the prosecution body in which the prosecutor holds a position, or reduction of the number of positions of prosecutors in the prosecution body, which, in the opinion of the court of constitutional jurisdiction, has a hidden legal consequence - dismissal of a prosecutor from the position held in the prosecution body, respectively.It is established that the peculiarities of legislative regulation of the power of the Prosecutor General to determine the structure of the prosecution bodies as one of the prerequisites for possible dismissal of a prosecutor from office in case of liquidation or reorganisation of the prosecution body in which the prosecutor holds a position, or in case of reduction of the number of prosecutors in the prosecution body, become the subject of indirect constitutional control, given the request formulated in the constitutional complaints of interested persons in this regard and the legal positions formed as a result of their resolution by the authorised jurisdictional bodies.It is noted that such peculiarities of legislative regulation of the Prosecutor General's powers have been recognised by the Constitutional Court of Ukraine as such which do not clearly define their scope and have a hidden legal consequence - dismissal of a prosecutor from the position held by him/her in the relevant prosecution body.The author identifies the prospects for legislative regulation of relations in the area under study, among which it is proposed to recognise as a priority the conceptual change in the legislative approach to the way of determining the structure of the prosecution bodies in Ukraine by means of its regulation by law in the development of the constitutionally determined trend of bringing the prosecution closer to the judiciary, and the status of a prosecutor closer to the status of a judge.